Optimasi Komposisi Makanan Pada Penderita Diabetes Melitus dan Komplikasinya Menggunakan Algoritma Genetika - Maryamah Maryamah; Rekyan Regasari Mardi Putri; Satrio Agung Wicaksono (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2017)
Diabetes Mellitus (DM) is the 4th largest cause of death in the world and causes more deaths than other diseases so needed serious attention is required. One that can be done is by diet therapy that is composing daily food menu. Diabetic diet is done with attention of energy, carbohydrates, proteins, and fats with precise and accurate. The calculation of the patient's energy can be done manually or with the help of a system that implements an algorithm. If done by manual process will take a long time especially if the available food is very much and diabetic diet every complication has different needs. With the help of computation process system will take place quickly and if applied a calculation algorithm will yield more optimal solution, one of the algorithm is genetic algorithm. Genetic algorithm is a heuristic method that is a search method, in implementation there are rules to obtain a better solution than the previous solution. Genetic algorithm is widely applied to various optimization problems so it is also expected to optimize the problem on the optimization of food composition. The results obtained from the research conducted are individuals in the optimal population of 250 individuals with the number of generations of 145 and the combination of cr and mr most optimal is 0.7 and 0.3 with fitnes 0. 01857.